ANALISIS PENGARUH EKONOMI MAKRO, STRUKTUR MODAL DAN KINERJA PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN LQ-45 DI BEI PERIODE 2013 – 2017 - Yuliana, Retno; Widarno, Bambang; Suharno, Suharno (Universitas Slamet Riyadi, 2019)
Stock prices fluctuate depending on the high demand on the stock market. Therefore, investors need to consider macroeconomic and microeconomic factors. This study aims to determine the effect of inflation, exchange rate of rupiah, interest rate, debt to equity ratio and return on assets toward the stock return either partially. The sample of this study was 34 LQ-45 companies listed on the Indonesia Stock Exchange for the period 2013 - 2017 which were obtained by purposive sampling method. Data analysis technique used descriptive statistical analysis, classic assumption test and multiple linear regression analysis.The results of the study partially indicate that the inflation variable, interest rate and debt to equity ratio have a negative and non-significant influence toward the stock returns, while the variables exchange rate of rupiah and return on assets have a positive and significant influence toward the stock return.